Orthopantomographic Survey of Hypodontia among Iraqi Orthodontic Patients - Lamia H Al-Nakib; Wasan H Younis
224 of orthodontic attainders of the Dental Polyclinic for Consultants of College of Dentistry / University of Baghdad aged 12-19 years were chosen to participate in this study. Orthopantomograph was taken for each patient and examined to detect the absence of teeth. The data were computed and statistically analyzed using SPSS version 7.5 computer software . The result revealed that 63 (28.1%) of individuals examined with varying degrees of hypodontia females 37 of 126 (29.4%) and 26 males of 98 (26.5%). The prevalence of congenital missing teeth if the third molar is excluded a total of 20 patients (8.9%) had hypodontia, 12 females (9.6%) and 8 males (8.1%). If third molar is considered alone 57 patients (25.4%) had one or more congenitally missing third molar. This study demonstrates the value of orthopantomograph in detecting or conforming dental abnormalities and supports the recommendations of the use of it, to aid the assessment of dental development.